Толерантність особистості, критерії її розвитку - Підбуцька, Ніна Вікторівна (НТУ "ХПІ", 2017)
Стаття присвячена аналізу поняття толерантності, його філософському, педагогічному та психологічному аспектів. Розглядається сутність та критерії толерантної поведінки особистості. Визначено, що суб'єктами толерантності є не тільки окремі особистості, але й великі та малі соціальні групи, інститути держави Також акцентується увага на необхідності формування толерантності у студентів, за допомогою якої стабілізуються міжособистісні відносини та розв’язуються конфліктні ситуації між людьми.

The article is devoted to the analysis of the concept of tolerance, its philosophical, pedagogical and psychological aspects. The essence and criteria of tolerant behavior of the person are considered. It is determined that the subjects of tolerance are not only individuals, but also large and small social groups, institutions of the state. Attention is also focused on the need for the formation of tolerance among students, through which interpersonal relations are stabilized and conflict situations between people are resolved. A tolerant personality must have such personal traits as humanity, reflection, freedom, responsibility, security, flexibility, self-confidence, endurance, variability, perception, empathy and sense of humor. Tolerance is the moral quality of the individual. It acts as an active form of interaction, connected with the search for what unites, not divides people.
Tolerance of the individual, criteria for his development
Keywords: студент; терпіння; конфлікт; tolerance; patience; personality; student